Pharmaceutical evaluation of atorvastatin-loaded nanostructured lipid carriers incorporated into the gelatin/hyaluronic acid/polycaprolactone scaffold for the skin tissue engineering. (March 2021) - Ahmadi, Mahsa; Mehdikhani, Mehdi; Varshosaz, Jaleh; Farsaei, Shadi; Torabi, Hadis
In this study, gelatin/hyaluronic acid (HA) scaffolds containing different amounts of atorvastatin-loaded nanostructured lipid carriers (NLCs) coated entirely with polycaprolactone (PCL) film were fabricated for skin regeneration. 12 atorvastatin-loaded NLCs formulations were synthesized, and particle size, zeta potential, drug entrapment efficiency (EE), and drug release of the formulations were determined. The optimum freeze-dried atorvastatin-loaded NLCs were added in 3 different weight percentages to the gelatin and HA membranous scaffolds. Thereafter, the membranes were coated entirely by a thin layer of the PCL. They were characterized, and then mechanical properties, in vitro degradation and in vitro drug release were assessed. Moreover, human dermal fibroblasts (HDF) were cultured on the prepared nanocomposite scaffolds in order to investigate the cytotoxicity by the MTT assay after the first day, third day, and fifth day. Results revealed that the most favorable atorvastatin-loaded NLCs had 99.54 nm average particle size, −24.30 mV zeta potential, 97.98% EE, and 75.24% drug release within 237 hrs. Mechanical tests indicated that all the three scaffolds had approximately a 90 MPa elastic modulus which was more than two-fold of tensile modulus of normal human skin. The in vitro degradation test demonstrated that the membranes were degraded up to 98% after 5 days, and the scaffolds drug release efficiency (DRE) was in a range of 75–79% during those 5 days. The MTT assay results confirmed the cytocompatibility of the scaffolds. The scaffold containing 54.1 wt% NCLs was the optimum sample (S3 ). Scanning Electron Microscopy (SEM) images of the latter one showed the uniform distribution of the NLCs with an average size of 150 nm, and the images of cultured HDF illustrated the good cell attachment. In conclusion, suitable physicochemical and biological properties of the novel gelatin/HA/PCL nanocomposite scaffold containing 54.1 wt% atorvastatin-loaded NLCs (S3 ) can be a good candidate for skin regeneration.